Metacognition Monitoring in Tasks that Involve Verbal Creativity - Deffendi, Luma Tiziotto (2017)
Metacognition involves the knowledge that individuals have with respect to their own cognitive processes, and includes self- monitoring, self-regulation and evaluation of their cognitive activities, including activities evolving creativity. The aim of this study was to investigate metacognitive monitoring among university students when performing tasks that involve verbal creative processes. Participants included 82 university students, who completed the Torrance’s Verbal Test of Creative Thinking. After finishing the creativity test, they were asked to evaluate their performance (metacognitive monitoring). The results suggest that the participants appear to have poor metacognitive monitoring skills in tasks involving creativity, sincethe correlation between actual and estimated performance was weak.